Specific prisoners' rights and their obligations as forms of human rights restrictions - В. О. Човган (Проблеми Законності, 2014)
This article examines such forms of restrictions on rights of prisoners as an obligation and a specific subjective right. Examples of how these forms of restrictions may appear in legislation are disclosed. It is shown that obligations of prisoners should be always considered as restriction of prisoners' rights. The cases in which a specific right can be recognized as a form of restriction on rights of prisoners are described.